1974
DOI: 10.1139/v74-146
|View full text |Cite
|
Sign up to set email alerts
|

Model Calculations of Kinetic Isotope Effects in Nucleophilic Substitution Reactions

Abstract: The results of calculations indicate that a previously proposed model for the transition state in "borderline" substitution reactions can be generalized and, as a result, the observed differences in the carbon-13 and deuterium isotope effects of S s l , Ss2, and "borderline" reactions rationalized. Although the conclusions may apply more generally, the standard reaction investigated is the solvolysis of benzyl bromide. The importance of resonance interaction with the phenyl ring, the significance of the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…bond order-force constant relationships we have employed for these basic models are given in Table 6. These models are very similar to the constant bond order models used previously (5,(13)(14)(15)40) but it should be noted that none of these transition states will fit all the kinetic isotope data for the methyl iodide-chloride ion system (17). The first calculations we will consider will be those for vL = 0 and for total bond order, n, = 1 = n, + n,, withF,, = +(FcclFc,)'12(see Table 5) where the force constants for the CI and the CCl bonds are given in Table 6.…”
Section: Reaction Coordinares and The Product-like (Reactant-like) Chsupporting
confidence: 64%
See 2 more Smart Citations
“…bond order-force constant relationships we have employed for these basic models are given in Table 6. These models are very similar to the constant bond order models used previously (5,(13)(14)(15)40) but it should be noted that none of these transition states will fit all the kinetic isotope data for the methyl iodide-chloride ion system (17). The first calculations we will consider will be those for vL = 0 and for total bond order, n, = 1 = n, + n,, withF,, = +(FcclFc,)'12(see Table 5) where the force constants for the CI and the CCl bonds are given in Table 6.…”
Section: Reaction Coordinares and The Product-like (Reactant-like) Chsupporting
confidence: 64%
“…In particular the value of 8 suggests that all these transition states are product-like in the RcB,-Roc plane, i.e., 8 is between -90" and -45". When n, is reduced to 0.45, the magnitude of v, decrea-ses as d o the isotope effects and the AX(C*)'s; however, we note that for n, = 0.4, 8 is positive, i.e., the reaction coordinate motion is symmetric stretch, 'As Bron has pointed out, such a model for an S,I reaction would only apply if no intermediates were involved in the reaction (15). It is now known that the S,1 category includes a rather large family of mechanistic possibilities (1 1, 12).…”
Section: Reaction Coordinares and The Product-like (Reactant-like) Chmentioning
confidence: 61%
See 1 more Smart Citation
“…Westaway and Ali have recently shown that the magnitude of the secondary adeuterium kinetic isotope effect can be related to the nucleophile -leaving group transition state distance in a closely related series of reactions (6). This is possible because the magnitude of secondary a-deuterium kinetic isotope effects in S,2 reactions is primarily determined by the differences in the energy of the C,-H(D) out-of-plane bending vibrations in the initial and transition states (31,34,35). Since the point of structural change is four bonds away from the C,-H(D) bond, the frequencies of the C,-H(D) out-ofplane bending vibrations are the same (1450 + 5 cm-I) for all theparrz-substituted benzyl chlorides used in this study.…”
Section: Secondary A-deuterium Kinetic Isotope Effectsmentioning
confidence: 99%
“…Furthermore, an accurate knowledge of p.f.r. 's in isotope effect calculations eliminates at least one of the many uncertainties inherent in these computations (6,26).…”
mentioning
confidence: 99%